Processus décisionnels, justice naturelle et équité procédurale dans la jurisprudence comparée de la Cour fédérale et des cours ontariennes et québécoises - Robardet, Patrick (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1982)
Natural justice and fairness (the « new natural justice ») are well known notions of administrative law. They constitute traditional and newer limits on administrative action. This article analyses these two principles, both as to their nature and the extent to which they are respected by administrative bodies and by government (the Crown and central departments). This latter aspect is illustrated by cases pertaining to the judicial control exercised by the Federal Court of Canada and the Ontario and Quebec superior courts. The approach followed is a comparative one. The paper attempts to identify those judicial trends within the three systems studied which [emphasize] [differences and similarities] in their responses to the various practical issues raised by natural justice and fairness and their respect in administrative decision-making processes. Thus, the study attempts to retrieve from the case law considered those notional and methodological elements, or principles, which structure judicial control and judical reasoning in solving the issues raised by the processes in motion.